Laboratory biochemical markers of cardiac injury by COVID-19: an integrative review. - Soares, Wagner Rodrigues de Assis; Andrade, Máyra Beatriz Alves; Oliveira, Anne Araújo de Jesus; Brito, Pedro Gabriel Santos; Miranda, Gabriel Novaes; Cardoso, Diego Rocha; Santos, Naiane Oliveira; Andrade, Bruno Silva (Saúde (Santa Maria), 2021)
The damaging effects of Sars-CoV-2 on cardiac tissue may be intensified with the presence of cardiocirculatory pathologies. The use of clinical biomarkers has grown, in order to monitor this cardiotoxicity early. In this sense, this study aimed to investigate, through an integrative review, the main biomarkers of cardiac injury associated with comorbidities in patients with COVID-19. A systematic bibliographic search was conducted on July 26, 2020, in the Scopus database. Of the total of 669 publications purchased, only 40 articles were eligible for this review. From the content of these publications, 16 systemic cardiac and inflammatory biomarkers that are part of the clinical findings of critically ill patients with COVID-19 were identified. Most of these patients were male, had a mean age of 63 years, and pre-existing comorbidities, such as were hypertension, diabetes mellitus, coronary artery disease, cerebrovascular disease, and chronic obstructive pulmonary disease. Cardiac injuries in patients infected with COVID-19 are related to the increase in cardiac and systemic biomarkers observed in most of these individuals. Finally, it is expected to increase physicians’ awareness of biochemical markers of non-invasive cardiac injury, for diagnosis and prognosis, of unusual extrapulmonary pathophysiological presentations during infection by COVID-19.